2011
DOI: 10.2131/jts.36.261
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke decreases organic acids levels and population of bifidobacterium in the caecum of rats

Abstract: -Cigarette smoke has been known to affect the development of bowel disease. However it has not been fully elucidated how cigarette smoke has effects on the gut. In this context we evaluated not only caecal levels of organic acids but also populations of micro-flora and pH in caecal contents after exposing rats (n = 5) to cigarette smoke for a 4-week in order to investigate whether the gut environment is altered by cigarette smoke or not. After the exposure of cigarette smoke, caecal levels of organic acids suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 16 publications
1
49
1
2
Order By: Relevance
“…The changes of proportion in organic acids in the gut are thought to be closely related with not only the inflammation in intestinal mucosa but also systemic effects in UC (Rodriguez-Cabezas et al, 2003). Recently, our study has demonstrated that cigarette smoke exposure to rats for 4 weeks altered the gut environment (Tomoda et al, 2011).…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…The changes of proportion in organic acids in the gut are thought to be closely related with not only the inflammation in intestinal mucosa but also systemic effects in UC (Rodriguez-Cabezas et al, 2003). Recently, our study has demonstrated that cigarette smoke exposure to rats for 4 weeks altered the gut environment (Tomoda et al, 2011).…”
Section: Introductionmentioning
confidence: 56%
“…The animals were compulsorily exposed to cigarette smoke using a tobacco smoke exposure apparatus (MIPS, Inc., Osaka, Japan) based on the method of Tomoda et al (2011). All smoke exposure experiments were carried out using filtered tipped Long Peace cigarettes (Japan Tobacco Industry Co., Ltd., Tokyo, Japan), the nicotine and tar contents of which are 2.3 mg and 28 mg per cigarette, respectively.…”
Section: Methods Of Cigarette Smoke Exposurementioning
confidence: 99%
“…smoke altered the gut environment (Tomoda et al, 2011). The increase in glutamine usage related to the alteration in the gut environment caused by cigarette smoke that may partially contribute to the decrease in skeletal muscle BCAA levels.…”
Section: Discussionmentioning
confidence: 99%
“…Animals were compulsively exposed to cigarette smoke using a tobacco smoke exposure apparatus (MIPS, Inc., Osaka, Japan) based on the method by Tomoda et al (2011Tomoda et al ( , 2012. The animals were provided the following 4 groups depending on whether they were exposed to the cigarette smoke and the diets they received: non-smoking/control diet, non-smoking/BCAA-rich diet, smoking/control diet, and smoking/BCAA-rich diet.…”
Section: Experimental Animals and Cigarette Smoke Exposurementioning
confidence: 99%
“…Currently, only a few studies in nonhuman animals have been published, but they do align with observations in humans, thereby highlighting the cigarette smoke (CS)-dependent shift in the gut microbiota structure. [62][63][64][65] Four weeks of CS exposure induced a decrease of the Bifidobacterium population in the rat cecum. 64 In mice, sidestream smoke exposure increased Clostridium spp.…”
mentioning
confidence: 99%